From Sources to Solution Proceedings of the International Conference on Environmental Forensics 2013 - Aris, A.Z.; Tengku Ismail, T.H.; Harun, R.; Abdullah, A.M.; Ishak, M.Y.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2014)
Featuring the theme, From Sources to Solution, this book is based on the research papers presented during the International Conference on Environmental Forensics 2013. It covers multi-disciplinary areas of environmental forensics featuring major themes: characterization, assessment, and monitoring; new approach, rapid assessment, and analytical techniques; pollution control technology; environmental health risk assessment; and policy, governance and management. It present information for researchers from the science and social sciences disciplines and contribute to the advancement of Environmental Forensics. It also aims at evaluating the environmental damages as the result of indiscriminating discharge of toxic environmental pollutants.
Environmental monitoring -- Analytical techniques -- Pollution control -- Environmental health -- Policy and Governance -- Data mining and environmental modelling.
Keywords: Environmental sciences; Environmental law; Environmental management; Environmental toxicology; Pollution; Environment; Environmental Monitoring/Analysis.; Environmental Science and Engineering; Environmental Management; Ecotoxicology; Environmental Law/Policy/Ecojustice.; Pollution, general